Differential effects of leptin on adiponectin expression with weight gain versus obesity - Singh, P; Sharma, P; Sahakyan, K R; Davison, D E; Sert-Kuniyoshi, F H; Romero-Corral, A; Swain, J M; Jensen, M D; Lopez-Jimenez, F; Kara, T; Somers, V K (International Journal of Obesity, 2016)
Background/Objective: Adiponectin exerts beneficial effects by reducing inflammation and improving lipid metabolism and insulin sensitivity. Although the adiponectin level is lower in obese individuals, whether weight gain reduces adiponectin expression in humans is controversial. We sought to investigate the role of weight gain, and consequent changes in leptin, on altering adiponectin expression in humans. Methods/Results: Forty-four normal-weight healthy subjects were recruited (mean age 29 years; 14 women) and randomized to either gain 5% of body weight by 8 weeks of overfeeding ( n =34) or maintain weight ( n =10). Modest weight gain of 3.8±1.2 kg resulted in increased adiponectin level ( P =0.03), whereas weight maintenance resulted in no changes in adiponectin. Further, changes in adiponectin correlated positively with changes in leptin ( P =0.0085). In-vitro experiments using differentiated human white preadipocytes showed that leptin increased adiponectin mRNA and protein expression, whereas a leptin antagonist had opposite effects. To understand the role of leptin in established obesity, we compared adipose tissue samples obtained from normal-weight versus obese subjects. We noted, first, that leptin activated cellular signaling pathways and increased adiponectin mRNA in the adipose tissue from normal-weight participants, but did not do so in the adipose tissue from obese participants. Second, we noted that obese subjects had increased caveolin-1 expression, which attenuates leptin-dependent increases in adiponectin. Conclusions: Modest weight gain in healthy individuals is associated with increases in adiponectin levels, which correlate positively with changes in leptin. In vitro , leptin induces adiponectin expression, which is attenuated by increased caveolin-1 expression. In addition, the adipose tissue from obese subjects shows increased caveolin-1 expression and impaired leptin signaling. This leptin signal impairment may prevent concordant increases in adiponectin levels in obese subjects despite their high levels of leptin. Therefore, impaired leptin signaling may contribute to low adiponectin expression in obesity and may provide a target for increasing adiponectin expression, hence improving insulin sensitivity and cardio-metabolic profile in obesity.